Influence of structural features and feruloylation on fermentability and ability to modulate gut microbiota of arabinoxylan in in vitro fermentation - Li, Zhongxia; Zhang, Huibin; He, Li; Hou, Yaqin; Che, Yingjuan; Liu, Tian; Xiong, Shaobai; Zhang, Xuguang; Luo, Shunjing; Liu, Chengmei; Chen, Tingting (Frontiers in Microbiology, 2023)
The objective of this study was to investigate the influence of arabinoxylan carbohydrate structural feature and feruloylation on fermentability and the effect of modulation of gut microbiota of arabinoxylan (AX). Arabinoxylans from rice bran and corn bran (RAX and CAX) and their deferulyolated counterpart dRAX and dCAX were fermented using an in vitro fermentation model. The AXs from rice have a higher A/X ratio than the AXs from maize, suggesting more branching and a more complex side chain. The structural difference was crucial for the difference in fermentation pattern. Different Bacteroides species are responsible for the utilization of rice AXs and corn AXs. Although feruloylation had a minor effect on the overall fermentation pattern, it significantly affected butyrate production and alpha diversity. dRAX promoted less butyrate than RAX, which is associated with a significantly lower amount of Faecalibacterium prausnitzi. dCAX promoted more butyrate than CAX, which may be associated with a lower amount of Bacteroides ovatus and a higher amount of Blautia in dCAX compared to CAX. The effects of feruloylation on the fermentation pattern and the resulted microbiota shift of AX varied depending on the carbohydrate structure.